Research progress in medication compliance among tuberculosis patients (肺结核患者服药依从性的研究进展) - JIANG Chengyu (江澄瑜) (中西医结合护理)
This paper reviewed the studies on the compliance with medication among tuberculosis patients, including the evaluation method of treatment compliance, influencing factors and the nursing countermeasures. This review aimed to provide reference for intervention on enhancing the clinical practitioner’s awareness of tuberculosis, improving their evaluation and management ability, and preventing the emergence of MDR-resistant tuberculosis due to the failure to follow the standard medication of tuberculosis treatment. This review also presented ideas for further scientific research and clinical practice. (本文就肺结核患者服用药物治疗依从性的相关研究进行总结, 包括服用治疗依从性的评估方式、影响因素及其提高服用治疗依从性的护理对策等。通过增强临床工作人员对肺结核患者治疗依从性的了解、评估和管理能力, 预防由于未遵循结核治疗规范标准用药而引起耐多药肺结核的出现, 并以此为护理临床工作和科学研究提供参考依据。)